2019
DOI: 10.1002/ece3.5425
|View full text |Cite
|
Sign up to set email alerts
|

Effects of taxon sampling and tree reconstruction methods on phylodiversity metrics

Abstract: The amount and patterns of phylodiversity in a community are often used to draw inferences about the local and historical factors affecting community assembly and can be used to prioritize communities and locations for conservation. Because measures of phylodiversity are based on the topology and branch lengths of phylogenetic trees, which are affected by the number and diversity of taxa in the tree, these analyses may be sensitive to changes in taxon sampling and tree reconstruction methods. To investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 67 publications
(138 reference statements)
0
46
0
Order By: Relevance
“…However, case studies have demonstrated that mode of phylogenetic inference has little influence on phylodiversity metrics. In other words, equivalent results have been obtained from purpose‐built and synthetic trees (Allen et al., 2019; Jantzen et al., 2019; Li, Trotta, et al, 2019). Nevertheless, the impact of limited sampling in a regional phylogeny on divergence times, using either a purpose‐built or pruned tree, compared to a global phylogeny remains to be assessed directly.…”
Section: Ages Derived From the Chinese Regional Phylogeny Do Not Biasmentioning
confidence: 71%
“…However, case studies have demonstrated that mode of phylogenetic inference has little influence on phylodiversity metrics. In other words, equivalent results have been obtained from purpose‐built and synthetic trees (Allen et al., 2019; Jantzen et al., 2019; Li, Trotta, et al, 2019). Nevertheless, the impact of limited sampling in a regional phylogeny on divergence times, using either a purpose‐built or pruned tree, compared to a global phylogeny remains to be assessed directly.…”
Section: Ages Derived From the Chinese Regional Phylogeny Do Not Biasmentioning
confidence: 71%
“…This is a welcome simplification, especially when dealing with hard to determine taxa. Second, phylogenetic diversity estimation using the clade indices requires less effort, expertise, and cost, as there is no need to obtain molecular data, performs a phylogenetic analysis and molecular dating (the latter is not necessary when phylograms are used, i.e., branch lengths in units substitutions per site; but see Jantzen et al, 2019 for discussion of how phylogenetic diversity measures can be affected by using either phylograms or dated phylogenies). As discussed in Li et al (2019), researchers have to decide what markers (Which genes to select?)…”
Section: Discussionmentioning
confidence: 99%
“…What fossil constraints for molecular dating?). All these difficult methodological decisions can be also avoided using phylogenies pruned from supertrees, for example, Daphne (Durka & Michalski, 2012) or the Open Tree of Life (Hinchliff et al, 2015), which have been shown to provide estimates of phylogenetic diversity well correlated to those derived from purpose‐built phylogenies (Li et al, 2019) and, additionally, have broader taxon sampling coverage that is important to correctly estimate phylogenetic diversity (Jantzen et al, 2019; Park et al, 2018). On the other hand, for many taxonomic groups, supertrees are poorly sampled and unavailable (e.g., Daphne covers only a part of the European flora) or do not include branch lengths (Open Tree of Life) that need to be additionally calculated (Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations